Pendampingan Penulisan Penelitian Tindakan Kelas (PTK) Guru Sosiologi di Musyawarah Guru Mata Pelajaran (MGMP) Sosiologi DKI Jakarta - Suyuti; Septiandini, Devi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The Community Service (PkM) activities that will be carried out with the Jakarta State University grant for the 2023 fiscal year depart from the road map of the research and community service program as an implementation of the tridarma of higher education at Jakarta State University related to the field of education, especially the development of teacher professionalism and the road map of the Sociology Education study program which aims to assist in writing class action research (PTK) for sociology teachers who are members of the DKI Jakarta subject teacher deliberation (MGMP). Through teacher communities such as MGMP, teachers can use it to improve the quality of teaching from preparation to evaluation and quality improvement through class action research. However, the problem that is currently present is that there are still few teacher communities that utilize the forum to improve their teaching capacity, one of which is experienced by teachers in the DKI Jakarta MGMP Sociology community. Therefore, in this community service activity, training on classroom action research will be carried out to improve the quality of learning by sharing experiences and knowledge related to classroom action research. This community service activity is in partnership with the Education Office and the DKI Jakarta MGMP Sociology Community. The process of activities that will be carried out by this service team with a mentoring system, mentoring activities begins with organizing focus group discussions to explore more deeply related to constraints and mapping the ability of teachers to make class action research. In mentoring, all teachers who are members of the DKI Jakarta Sociology MGMP will participate. It is expected that the output of this activity will result in a mentoring video on YouTube, teacher work, and intellectual property rights from making class action research